A survey of feature modeling methods: Historical evolution and new development. (February 2020) - Li, Lei; Zheng, Yufan; Yang, Maolin; Leng, Jiewu; Cheng, Zhengrong; Xie, Yanan; Jiang, Pingyu; Ma, Yongsheng
Highlights: The historical evolution of feature modeling methods is reviewed in this paper. The interoperability issue has been identified as a key challenge and a thorough review is conducted. The focus of this survey is on the state of the art application of features in the emerging research fields. In addition to the modeling of a single product, the capability of features should be enhanced to model advanced manufacturing systems. Abstract: Initially developed for geometric representation, feature modeling has been applied in product design and manufacturing with great success. With the growth of computer-aided engineering (CAE), computer-aided process planning (CAPP), computer-aided manufacturing (CAM), and other applications for product engineering, the definitions of features have been mostly application-driven. This survey briefly reviews feature modeling historical evolution first. Subsequently, various approaches to resolving the interoperability issues during product lifecycle management are reviewed. In view of the recent progress of emerging technologies, such as Internet of Things (IoT), big data, social manufacturing, and additive manufacturing (AM), the focus of this survey is on the state of the art application of features in the emerging research fields. The interactions among these trending techniques constitute the socio-cyber-physical system (SCPS)-based manufacturing which demands for feature interoperability across heterogeneous domains. Future efforts required to extend feature capability in SCPS-based manufacturing system modeling are discussed at the end of this survey.